Spinoza's 'Ethics' : a critical guide - Melamed, Yitzhak Y., 1968- (New York : Cambridge University Press, 2017)
Spinoza's Ethics, published in 1677, is considered his greatest work and one of history's most influential philosophical treatises. This volume brings established scholars together with new voices to engage with the complex system of philosophy proposed by Spinoza in his masterpiece. Topics including identity, thought, free will, metaphysics, and reason are all addressed, as individual chapters investigate the key themes of the Ethics and combine to offer readers a fresh and thought-provoking view of the work as a whole. Written in a clear and accessible style, the volume sets out cutting-edge research that reflects, challenges, and promotes the most recent scholarly advances in the field of Spinoza studies, tackling old issues and bringing to light new subjects for debate.
Machine generated contents note: 1. The indiscernability of identicals and the transitivity of identity in Spinoza's logic of the attributes Don Garrett; 2. Spinoza and Maimonides on teleology and anthropocentrism Warren Zev Harvey; 3. Two puzzles about thought and identity in Spinoza John Morrison; 4. Spinoza and the mark of the mental Martin Lin; 5. The 'physical' interlude Alison Peterman; 6. The causes of our belief in free will: Spinoza on necessary, 'innate', yet false, cognition Yitzhak Melamed; 7. Conatus John Carriero; 8. Scientia intuitiva in the Ethics Kristin Primus; 9. Causa conscientiae' in Spinoza's Ethics Lia Levy; 10. Spinoza on the association of affects and the workings of the human mind Lisa Shapiro; 11. The terminology of the affects in Ethics parts three through five Pina Totaro; 12. Moral realism in Spinoza's Ethics Colin Marshall; 13. Spinoza and the metaphysics of perfection Samuel Newlands; 14. The free man and the free market: ethics, politics, and economics in Spinoza's Ethics IV Beth Lord; 15. Spinoza and the power of reason Michael LeBuffe.
Title from publisher's bibliographic system (viewed on 07 Jul 2017).
Keywords: 1632-1677. -- Ethica; Electronic books